PLANTAS TÓXICAS PARA ABELHAS - Cintra, P. [UNESP]; Malaspina, O. [UNESP]; Bueno, O. C. [UNESP] (Instituto Biológico, 2022)
This review cover's some data from studies about toxic plants. There are plants that produce toxic pollen or nectar, and these plants were used in laboratory bioassays, confirming toxic effects against bees. Most of information on chemical structures of toxins and their effects on insects and mammals has been obtained from research. Such knowledge can help us to discover the chemical nature of bee poisoning by these plants.

Esta revisão tem por objetivo agrupar os dados referentes ao estudo das plantas tóxicas para abelhas. São relacionados os mais importantes artigos publicados sobre o assunto, principalmente os de autores brasileiros, confirmando os efeitos tóxicos do pólen ou néctar sobre estes insetos. As informações sobre as estruturas químicas de substâncias isoladas das diversas partes das plantas e sua atividade biológica, têm auxiliado muito na identificação dos mecanismos da intoxicação das abelhas por estas plantas.
PLANTS TOXIC TO BEES
Keywords: Bees; poisoning; plants; toxicity; pollen; nectar; Abelhas; envenenamento; plantas; toxicidade; pólen; néctar